Pengembangan Kurikulum PAUD (StudiKasus di PAUD Citra KartiniDesa Senggreng – Kecamatan.Sumber Pucung - Kabupaten Malang) - Yulianti, Hartatik, & Ninik Indawati (Universitas Kanjuruhan Malang, 2013)
Curriculum development in the learning process in any educational institution is to be done by each school. Early childhood education (PAUD) is the level of education before primary education which is a development effort aimed at children from birth to the age of six years are done through the provision of educational stimulation to assist the growth and development of children's physical and spiritual so has the readiness to enter further education, which was held in formal, non-formal, and informal. It is a fairly heavy targets for teachers in organizing the teaching process that must be followed by students. Currently still learning meaningful done. resulting in less motivated students to learn the material as indicated by the attitude of bored following the learning process so that the material is less memorable in their minds. Therefore, it is necessary to do research with the aim of describing (a) learning approach according to the stage of intellectual development of students and (b) can provide meaning for students to be able to become fully human. Manifold qualitative descriptive study of single case studies. Researchers at the same time acting as an instrument of data collection, which is required in the field. Method of data collection is done by three techniques, namely (1) in-depth interviews (in-depth interview), (2) observation, and (3) documentation. The process of collecting and analyzing the data of this study guided by the steps of qualitative research data analysis. Conclusion The study showed the following results: 1) Overview of the Institute of Image Kartini Village ECD Senggreng - District of source Pucung - Malang Regency, and 2) Implementation of the Curriculum Development Concept image of Kartini in early childhood learning method with the approach of Beyond Centers and Circle Time (BCCT).Â Keywords : Curriculum Development , PAUD